Surgical Treatment of a Giant Liposarcoma in a Japanese Man - Yasuhiro Hashimoto; Shingo Hatakeyama; Tokushi Tachiwada; Takahiro Yoneyama; Takuya Koie; Noritaka Kamimura; Takeshi Yanagisawa; Kenichi Hakamada; Chikara Ohyama (Advances in Urology)
We report a case of a rapidly progressing giant retroperitoneal liposarcoma weighing 22 kg in a 41-year-old Japanese man, successfully treated with surgical excision. To our knowledge, this is the largest liposarcoma in the Japanese population reported in the literature.